Numerical Simulation and Hazard Analysis of Debris Flows in Guxiang Gully, Tibet, China - Tang, Jinbo; Liu, Chen; Mao, Jiajie; Wang, Hao (Frontiers in Earth Science, 2022)
Guxiang gully, located in Bome county in southwest Tibet, China, is a right tributary of the Purlung Tsangpo River. Hanging glaciers are widely distributed upstream of the gully and a large number of moraines can cause debris flows triggered by run-off generated by the rainstorm and by melting water of glaciers are deposited in this gully. The debris flow in the Guxiang gully can frequently pose a serious threat to the Sichuan-Tibet Highway. Due to the unavailability of field observation data, in this study, the flood discharge method combining the run-off generated by the rainstorm and by melting water of glaciers was employed to determine the magnitudes of debris flow for under once-in-a-century, once-in-two-century, and once-in-three-century flood return periods. Furthermore, the numerical simulation is implemented to determine the maximum flow depth and velocity of debris flow in each grid cell, and the inundated debris flow area in Guxiang gully with different frequencies. Subsequently, each grid cell's maximum flow depth and velocity are used to assess buried hazards and impact hazards, respectively. The integrated hazard could be calculated by combining the buried hazard and the impact hazard. The result shows that the hazard of the top of the fan and Purlung Tsangpo River affected by debris flow is highest, and debris flow is likely to block the Purlung Tsangpo River.